Fostering effective student-centered learning beyond the class - Jayasingh Chellamal, Hanish Singh; Mohd Hatta, Fazleen Haslinda; Jahidin, Aisyah Hasyila; Mohamed, Ruzianisra; Abdullah, Zafirah Liyana; Karuppanan, Mahmathi (Faculty of Pharmacy, 2025)
This program was conducted for the staff of the Faculty of Pharmacy, UiTM on 19th March 2025. In light of imparting additional knowledge to our teaching experts, for the facilitation of case-based learning/ problem-based learning and other teaching methodologies, this program was led by three experts from the medical education field.